Analysis of EEG trials with external tactile stimulus-identification and rejection of artifacts using EEGLAB - Sng, Brian Wen Hao (2018)
Since the 20th century, neuroscience has seen a resurgence in the research field with technological advances. EEG, an electrophysiological monitoring method was first introduced in 1912 and was conducted on animals. It is now certified to be used on humans and multiple software have been created to analyse data from EEG. One such software is a package by MATLAB, called EEGLAB. Analysis of EEG recordings by subjects undergoing tactile stimuli on their fingers will be done by EEGLAB. This will include identification and subsequent rejection of artifacts present in the EEG recordings. This report aims to utilise EEGLAB’s inbuilt functions such as applying basic Finite Impulse Response(FIR) filter of 7-13Hz, Independent Component Analysis(ICA) to produce individual channel plots and component maps to get information about the brain when subjected to an external stimulus which requires the subject to touch surfaces of different roughness.